Nearly 100% Horizontal Dipole Orientation and Upconversion Efficiency in Blue Thermally Activated Delayed Fluorescent Emitters. Issue 15 (22nd May 2018) - Byeon, Sung Yong; Kim, Jongchan; Lee, Dong Ryun; Han, Si Hyun; Forrest, Stephen R.; Lee, Jun Yeob
Abstract: The relationship between anisotropic orientation and molecular structure of thermally activated delayed fluorescent (TADF)‐based organic light emitting devices (OLEDs) is studied using TADF emitters with carbazole, biscarbazole, and triscarbazole donor units. The bicarbazole and triscarbazole donors are more effective than the carbazole donor in driving the anisotropic orientation of the TADF molecules. A near‐perfect in‐plane orientation of the TADF dipole moment is demonstrated using the triscarbazole donor. In addition, the triscarbazole donor based OLED shows high photoluminescence quantum yield and an upconversion efficiency close to 100%. As a consequence, an external quantum efficiency >30% is obtained. Abstract : A systematic study correlating donor structure with horizontal dipole orientation of blue triscarbazole thermally activated delayed fluorescent (TADF) emitters shows an exceptionally high horizontal dipole orientation of 95%. The dipole orientation and high photoluminescence quantum yield result in an external quantum efficiency >30% in organic light‐emitting diodes employing these TADF emitters.